Evaluación de los beneficios del centro de interpretación ambiental para el bosque de protección Alto Mayo – Sector Venceremos - Tuesta Gonzales, Carla Carol (2012)
The Environmental Center lnterpretation has become a useful and important tool for the care and education of visitors and inhabitants of the Venceremos sector knowing the importance of the conservation and study of the natural resources in your area. The evaluation of the Environmentat Center Interpretation (CIA), it allows to know the basic infrastructure, the services that drink, the economic, social and environmental benefits that the center of interpretation is generating in the sector whicb must be strengthened to ensure its sustainability with economic altematives in harmony with the forest, to achieve this should be well defined the responsibilities of the different actors and especially ensuring the participation of society .now we will defeat the sector increased its economic activity since the implementation ofthe CIA Also the population of the V enceremos Sector, is organized more, appreciates and knows the dynamics of the Alto Mayo Protection F orest (BP AM), reflected in the reduction of 4% of the extraction of natural resources generating a positive dynamism with tendency to continue to grow, the proposal shall be considered irnportant to sustainability as: the implementation of an area for the marketing ofhandicrafts, charging for admission to the CIA, as a way to promote the realization of complementary economic activities that would help to mitigate the negative impact of local populations on the BP AM, which will ensure its permanence in time. Key words: natural resources, environmental benefits